Life Cycle Assessment Applications To The Dry Steam Geothermal Power Generation (Case Study: Star Energy Geothermal Wayang Windu, Ltd, Indonesia) - Rina Annisa; Benno Rahardyan (Indonesian Journal of Life Cycle Assessment and Sustainability, 2018)
Geothermal potential in Indonesia estimate can produced renewable energy 29 GW, and until 2016 it still used 5% or about 1643 MW in. From that result, about 227 MW produced by Wayang Windu geothermal power plant. The Input were raw material, energy and water. These input produced electricity as main product, by product, and also other output that related to environment i.e. emission, solid waste and waste water. All environmental impacts should be controlled to comply with environmental standard, and even go beyond compliance and perform continual improvement.  This research will use Life Cycle Assessment method based on ISO 14040 and use cradle to gate concept with boundary from liquid steam production until electricity produced, and Megawatt Hours as the functional unit. Life Cycle Inventory has been done with direct input and output in the boundary and resulted that subsystem of Non Condensable Gas and condensate production have the largest environmental impact. LCI also show that every MWh electricity produced, it needed 6.87 Ton dry steam or 8.16 Ton liquid steam. Global Warming Potential (GWP) value is 0.155 Ton CO2eq./MWh, Acidification Potential (AP) 1.69 kg SO2eq./MWh, Eutrophication Potential (EP) 5.36 gPO4 eq./MWh and land use impacts 0.000024 PDF/m2. Life Cycle Impact Assessment resulted that AP contribute 78% of environmental impact and 98% resulted from H2S Non Condensable Gas. Comparison results with another dry steam geothermal power plant show that impact potential result of the company in good position and there’s a strong relation between gross production, GWP and AP value.Keywords: Life cycle assessment; Geothermal; Continual Improvement; Global Warming Potential; Acidification Potential